Pretend - Plecas, Jennifer (New York : Philomel Books, 2011)
A father and son embark on an imaginary adventure and discover how much they love each other
004-008
Keywords: Imagination -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Imagination -- Fiction; Fathers and sons -- Fiction